(untitled) (Mustansiria Dental Journal, 2018)
Background: Many researches indicated that magnetic field had effect on clotting time and serum calcium level when it was used for stimulation of bone healing and growth. This in vivo study was carried out to evaluate the effect of local pulsed magnetic on clotting time and serum calcium level when used for stimulation of intraosseous implant. Materials and Methods: Forty eight oryctologus cuniculus male rabbits were used in this study, they divided into two controlled groups and two experimental groups and each group consist of 12 animals, all experimental groups exposed to (50 gauss) pulsed magnetic field strength. Clotting time and calcium level measured at intervals of time (2, 4, 6and 8) weeks of healing periods. Results: the result indicated that theirs no significant differences between the controlled group and other groups for (50 Gauss) pulsed magnetic field which indicate no harmful effect of magnetic field on clotting time and calcium level. Conclusion: The use of (50 Gauss) pulsed magnetic field show no noticeable affect on serum calcium level and clotting time.